Pengaruh Brain-Based Learning terhadap Kemampuan Berhitung Dasar pada Siswa Autis Kelas 7 - Wulandari, Anita Astiarum; Emyus, Ahmad Zaki; Yaum, Lailil Aflahkul (JOEAI (Journal of Education and Instruction), 2025)
This study aims to determine the effect of the Brain-Based Learning (BBL) model on the basic arithmetic skills of seventh-grade autistic students at the Branjangan Special Needs School in Jember. The research method employed was a quantitative approach with a Single-Subject Research (SSR) design, utilizing an A-B design. The subject was a seventh-grade autistic student who exhibited difficulties in arithmetic. The results showed a significant increase from the average percentage in the baseline phase (28%–36%) to 60%–80% in the intervention phase. The absence of overlap between baseline and intervention data (0%) and the upward trend (+) indicate that the BBL model has a positive effect on improving the basic arithmetic skills of seventh-grade autistic students at the Branjangan Special Needs School in Jember.   Keywords: Brain-Based Learning, Basic Arithmetic Skills, Autistic Students